Le formiche e le stelle. Note sul leopardismo di Giuseppe Tomasi di Lampedusa - Colombo, Paolo (Rivista Internazionale di Studi Leopardiani, 2022)
The essay aims to draw a comparison between Giacomo Leopardi and Giuseppe Tomasi di Lampedusa. Moving from a general survey on the several mentions of the poet in the prince’s literary production, the paper will then propose a study on themes (death, youth, human misery, vanity of pleasure, astronomy) and attitudes (skepticism, wit, satire) that, more than others, appear to show an authentic intersection of the two authors.